Efisiensi, Value Added dan Produktivitas Tenaga Kerja UMKM Industri Abon Ikan Bandeng di Kota Tarakan - Devi, Charitin; Setiawan, Rusdy (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2024)
This research measures the efficiency, value-added, and labor productivity of 17 MSMEs in the milkfish floss industry in Tarakan City. Data processing efficiency using EMS, added Value using the Hayami model, and labor productivity using the BPS formula. Conclusions from the research: (1) only 1 MSME has an efficient production level, 16 MSMEs are inefficient; (2) there are 13 MSMEs whose production does not produce added Value, 4 MSMEs with 1 MSME with high added Value, 3 MSMEs with medium added Value; (3) there are 4 MSMEs with labor productivity around IDR. 45.312 to IDR. 176.000 in each production, 13 other MSMEs cannot be counted.